Modernization of Marketing Through Product Attributes and Promotions as An Effort to Preserve Tradisonal Minangkabau Spices: Ecotourism - Putri, Atika Dwi; Rino (Jurnal Penelitian Pendidikan IPA, 2023)
In an increasingly advanced era of globalization, technological developments sophisticated and slowly entering people's lives creates many conveniences. One of them is development, the internet which plays an important role nowadays covers various fields including the world of entertainment, the world of education, and the world of marketing. one of them is marketing through product attributes and promotions as an effort to preserve traditional Minangkabau spices: Ecotourism. This study aims to analyze the implementation of traditional product marketing with a modern marketing approach so that it is not left behind compared to other products coupled with the entry of imported products. UD. Boembu mandeh is a business that produces traditional Minangkabau spices inherited from our ancestors. This research is the result of field study activities carried out using qualitative methods based on observation, interviews and documentation of the research object. The results of this study indicate that the existence of traditional products must still adopt a modern marketing model for the products offered, especially in this study related to product attributes and product sales media by utilizing marketplace electronics commerce and social media.